The formerly incarcerated, advocacy, activism, and community reintegration - Smith, Justin M. (Contemporary justice review, 2021)
Restorative, or strength-based, reentry has been advanced as an alternative to the far more common risk-based or needs-based approaches to assisting in the reintegration of prisoners back into society. Drawing from restorative justice principles of repair, including key stakeholders, and transformation, this perspective illustrates how formerly incarcerated people work toward destigmatization and redemption by helping others (going the ‘second mile’ in the transformation process). Further, the formerly incarcerated lead and participate in social and political activism (the ‘third mile’) which provides them space to ‘make good’ and practice sharing their narratives as public testimonials. Using in-depth interviews with nine formerly incarcerated advocates and activists in Michigan, this study describes forms of (1) helping others and (2) participation in activism among the formerly incarcerated, and (3) blends theoretical analysis about how these actions affect the formerly incarcerated themselves.